The Association of Lipoprotein Lipase Genes, HindIII and S447X Polymorphisms With Coronary Artery Disease in Shiraz City - Zeinab Ahmadi; Sara Senemar; Samaneh Toosi; Salma Radmanesh (Journal of Cardiovascular and Thoracic Research, 2015)
Introduction: Several polymorphisms at the lipoprotein lipase (LPL) locus are associated with variations in LPL activity serum lipid concentrations and the risk of coronary artery disease (CAD). The aim of this study was to investigate the role of the LPL S447X and Hind III polymorphism in a sample of subjects with CAD and compare them with healthy subjects. Methods: The study enrolled 115 patients and 89 healthy subjects who were recruited from Namazi hospital in 2010-2012. The presence of two common polymorphisms of the LPL gene(HindIII and S447X) was determined by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) analysis using genomic DNA. SPSS 16.0 was used for statistic alanalysis. Results: S447X was significantly different between the patients with CAD and the healthy subjects (P<0.001). But HindIII was not significantly different between the patients with CAD and the healthy subjects (P=0.741). Risk factors such as smoking, hypertension, hyperlipidemia,triglyceride (TG) and high-density lipoprotein (HDL) levels had a significant association with CAD.Conclusion: In our study, the presence of G allele S447X polymorphism increases the TG level and decrease HDL level, so it increases the susceptibility CAD. Moreover, HindIII polymorphism did not have any significant association with CAD. Conclusion: In our study, the presence of G allele S447X polymorphism increases the TG level and decrease HDL level, so it increases the susceptibility CAD. Moreover, HindIII polymorphism did not have any significant association with CAD.